(untitled) (Nonconventional Technologies Review, 2021)
The first achieving in Romania of a self-aspirating burner using the nonconventional technique of burning in a porous inert media is presented in the paper. The originality of the work is the way of manufacturing the porous ceramic piece in the combustion zone of the burner by using the nonconventional method of producing a SiC ceramic foam by direct microwave heating. The main characteristics of the ceramic piece are: porosity of 36.8%, compressive strength of 58 MPa and operating temperature of 1430 ºC. The burner was made for operation with natural gas with a nominal thermal power of 20 kW. The concentration of pollutants emitted into the atmosphere is low: CO below 120 mg/m3N and NOx below 1.03 mg/m3N.